The Impact of Aging on the Association Between Aortic Stiffness and Cerebral Pulsatility Index - Fico, Brandon G.; Miller, Kathleen B.; Rivera-Rivera, Leonardo A.; Corkery, Adam T.; Pearson, Andrew G.; Eisenmann, Nicole A.; Howery, Anna J.; Rowley, Howard A.; Johnson, Kevin M.; Johnson, Sterling C.; Wieben, Oliver; Barnes, Jill N. (Frontiers in Cardiovascular Medicine, 2022)
The central arteries dampen the pulsatile forces from myocardial contraction, limiting the pulsatility that reaches the cerebral vasculature, although there are limited data on this relationship with aging in humans. The purpose of this study was to determine the association between aortic stiffness and cerebral artery pulsatility index in young and older adults. We hypothesized that cerebral pulsatility index would be associated with aortic stiffness in older adults, but not in young adults. We also hypothesized that both age and aortic stiffness would be significant predictors for cerebral pulsatility index. This study included 23 healthy older adults (aged 62 ± 6 years) and 33 healthy young adults (aged 25 ± 4 years). Aortic stiffness was measured using carotid-femoral pulse wave velocity (cfPWV), while cerebral artery pulsatility index in the internal carotid arteries (ICAs), middle cerebral arteries (MCAs), and basilar artery were assessed using 4D Flow MRI. Cerebral pulsatility index was calculated as (maximum flow – minimum flow) / mean flow. In the combined age group, there was a positive association between cfPWV and cerebral pulsatility index in the ICAs (r = .487; p < 0.001), MCAs (r = .393; p = 0.003), and basilar artery (r = .576; p < 0.001). In young adults, there were no associations between cfPWV and cerebral pulsatility index in any of the arteries of interest (ICAs: r = .253; p = 0.156, MCAs: r = -.059; p = 0.743, basilar artery r = .171; p = 0.344). In contrast, in older adults there was a positive association between cfPWV and cerebral pulsatility index in the MCAs (r = .437; p = 0.037) and basilar artery (r = .500; p = 0.015). However, the relationship between cfPWV and cerebral pulsatility index in the ICAs of the older adults did not reach the threshold for significance (r = .375; p = 0.078). In conclusion, age and aortic stiffness are significant predictors of cerebral artery pulsatility index in healthy adults. This study highlights the importance of targeting aortic stiffness in our increasingly aging population to reduce the burden of age-related changes in cerebral hemodynamics.